2018
DOI: 10.1002/jbmr.3399
|View full text |Cite
|
Sign up to set email alerts
|

Sex-, Ethnic-, and Age-Specific Centile Curves for pQCT- and HR-pQCT-Derived Measures of Bone Structure and Strength in Adolescents and Young Adults

Abstract: There are presently no adolescent centile curves for bone parameters at the tibial midshaft using peripheral quantitative computed tomography (pQCT) or at the distal radius and tibia using high-resolution pQCT (HR-pQCT). Thus, we aimed to develop sex-, ethnic-, site-, and age-specific centile curves for pQCT and HR-pQCT-derived bone outcomes for youth and young adults aged 10 to 21 years. We acquired pQCT scans (XCT3000 or XCT2000) at the tibial midshaft (50% site) and HR-pQCT scans (XtremeCT) at the distal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 50 publications
0
44
1
Order By: Relevance
“…Image analyses (standard and advanced cortical evaluation) have been developed for mature bone, but it is unknown how accurately these methods capture immature bone properties. (28,43) Ct.BMD and Ct.TMD values reported in our study and other pediatric studies (1)(2)(3)15,17) appeared about 35% lower than those reported for young and older adults. (28,43) This difference can be partly explained by lower density in immature bone based on growth and newly formed bone tissue and partial volume effects when scanning small bones of children.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…Image analyses (standard and advanced cortical evaluation) have been developed for mature bone, but it is unknown how accurately these methods capture immature bone properties. (28,43) Ct.BMD and Ct.TMD values reported in our study and other pediatric studies (1)(2)(3)15,17) appeared about 35% lower than those reported for young and older adults. (28,43) This difference can be partly explained by lower density in immature bone based on growth and newly formed bone tissue and partial volume effects when scanning small bones of children.…”
Section: Discussioncontrasting
confidence: 83%
“…Our small sample size limited between sex comparisons of annual changes, precision errors, or MTIs. Second, inherent to any prospective scanning of growing bone, we could not scan the exact same anatomical site at the baseline and follow‐up scan because of bone growth . Third, our FE model assumed fixed, homogeneous material properties for growing cortical and trabecular bone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations